Reformulasi Sistem Pendidikan Pesantren dalam Mengantisipasi Perkembangan Global - Zamroni, Zamroni (Dinamika Ilmu, 2011)
Islamic Boarding School (Pesantren) is the most autonomous institution that can not be on the intervention of any parties. In Islamic Boarding Schools, Kiai has authority in characterizing many activities of pesantren community. Variations of education is also due to differences in conditions sosi-cultural society that surrounds it. Development of the pesantren as an institution engaged in education and socio-religious, must be encouraged. Development of Pesantren must be continued cause of the change of world drastic and dynamic with rapid development, Of course, either directly or indirectly may affect to pesantren. In order for schools to continue to survive, then a few steps can be taken with the strategic development kept the same boarding school as an institution indegious Islamic education in Indonesia.